Diagnóstico de enfermedades más comunes del apiario apícola Centro Experimental CEASA - Caisabanda Masaquiza, Pacha Cutic (2019)
In the apiary beekeeping experimental center “CEASA” was diagnosed diseases to which bees are exposed of the hives because this species of insect is in the environment subject to a great diversity of macroscopic and microscopic living beings that many of them can be vectors of diseases in bees, for which a laboratory test was developed consisting of taking a sample of bees (between 300 to 500) from several frames and introduce it in a 25% ethanol solution, after a brief stirring the bees will be separated from the alcohol and and are displayed in this the mites that have come off their host;that have come off their host are visualized therein; and a field test to determine the level of honeycomb infestation, a direct examination of 50 sealed worker cells was performed. Each cell was detached and the brood (pupa) was checked thoroughly, as well as the inside of the cell. In this way it was determined that in the 10 hives, 5 were infested with Varroa between 17.98 and 35.29%, in terms of the prevalence of Nosemosis in the colonies in the same way it demonstrates infestations of 17.98 to 35% and in relation to American and European foulbrood, it was not registered in this study. Concluding that the prevalence of varroa in hives of CEASA in adult bee and bee breeding respectively was: 2.83%, and of the nosemosis of 24.15% being considered as low and easy to control, it is recommended that disease control is important to avoid low productivity in this species of zootechnical interest.